Ferdinand Saussure's Semiotic Analysis of the Politicization of Social Assistance in the Film Dirty Vote - Marzuki, Nur Rofifah; Sonni, Alem Febri; Arianto, Arianto (IHSA Institute, 2025)
This study analyzes the politicization of social assistance in the film Dirty Vote using Ferdinand de Saussure's semiotic approach. The concept of signifier and signified is used to identify and interpret the visual and verbal signs presented in the film. The results of the analysis show that elements such as party symbols, dominant colors, budget graphs, and narrative scenes illustrate the close relationship between the distribution of social assistance and certain political agendas. Signifiers such as the overlay text